Employee Performance Model: Analysis Of Information Technology Utilization, Knowledge Transfer And Knowledge Management - Apriani, Ari; Jumanto, Jumanto (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
The Promotion and Information Sub-Division has the task of carrying out part of the duties of the Lampung Provincial Liaison Agency in Jakarta related to the promotion and information and services of Anjungan Lampung Taman Mini Indonesia Indah (TMII). Some factors cause a lack of improvement in performance due to ineffective use of technological facilities. This is indicated by the results of the 2020 performance report during the COVID-19 pandemic, where the government issued a work-from-home (WFH) policy. The performance report data for the Lampung Province Liaison Agency in 2020 did not meet the target. This is caused by several factors, one of which is the use of information technology. Performance report data for 2020 - 2021 shows the results of employee performance reports, where the performance indicators in the Promotion and Information Sub-Sector have decreased. To solve the problem of improving performance caused by several factors, it is of particular concern to conduct research. All 50 employees of the Promotion and Information Subdivision are the population in this study. The sampling method used was a saturated sample approach. The data in this study were collected through a questionnaire using a Likert scale, and quantitative analysis was carried out using the SPSS analysis tool. The results showed a significant and positive correlation between Information Technology Utilization and Knowledge Transfer with employee performance. However, Knowledge Management has no impact on employee performance.Keywords: Employee Performance; Information Technology Utilization; Knowledge Management; Knowledge Transfer